Allocating and managing software assets (2013)
Among other disclosed subject matter, a computer program product is tangibly embodied in a computer-readable storage medium and includes instructions that when executed by a processor perform a method for allocating assets. The method includes assigning each of multiple operation sectors defined by a software program to respective ones of multiple load groups, each load group grouping at least one operation sector for loading assets of the operation sector into memory. The method includes assigning all assets from the multiple operation sectors into respective ones of multiple clusters based on associations between the respective assets and the multiple operation sectors. The method includes generating and storing a memory layout that assigns one of multiple memory locations to each of the multiple clusters for at least one of the multiple load groups.